(untitled) (Research, Society and Development, 2021)
Chronic exposure to pesticides can lead to disease and the scarcity of information on clinical manifestations and long term poisoning is a current concern. The aim of this work was to analyze the chronic use of pesticides of the fungicide class by a population of wine grower workers from a southern region of Brazil. A hundred and ninety-two family farmers were interviewed with instruments developed according to the protocol for the evaluation of chronic poisoning by pesticides of the Paraná State Department of Health. Among the participants, 45.8% worked in viticulture for over 20 years, continuously using fungicides, and only 6.8% used all protective equipment recommended for pesticide application. There were reported symptoms such as itchy skin irritation (20.5%) and tremors (12.1%) that may be associated with the chronic exposure to dithiocarbamate fungicides. The population of family farmers lacks health care, a fact also reported by the population studied. This highlights failures in the care service and the need for new strategies and technologies to access this group.